Loa loa vectors Chrysops spp.: perspectives on research, distribution, bionomics, and implications for elimination of lymphatic filariasis and onchocerciasis - Kelly-Hope, Louise (2017)
Loiasis is a filarial disease caused Loa loa. The main vectors are Chrysops silacea and C. dimidiata which are confined to the tropical rainforests of Central and West Africa. Loiasis is a mild disease, but individuals with high microfilaria loads may suffer from severe adverse events if treated with ivermectin during mass drug administration campaigns for the elimination of lymphatic filariasis and onchocerciasis. This poses significant challenges for elimination programmes and alternative interventions are required in L. loa co-endemic areas. The control of Chrysops has not been considered as a viable cost-effective intervention; we reviewed the current knowledge of Chrysops vectors to assess the potential for control as well as identified areas for future research.